When should MRSA eradication be attempted for patient with colonization or infection?. Issue 2 (February 2015) - Farris, Ryan; Geurin, Michael
Abstract : Evidence‐Based Answer : Hospitalized surgical and dialysis patients who are carriers of methicillin‐resistant Staphylococcus aureus (MRSA) should be considered for decolonization with mupirocin to prevent nosocomial S aureus infections (SOR: A, meta‐analysis). However, studies specifically in patients with MRSA have not shown benefit (SOR: B, small RCTs). A focus on hygiene is recommended to prevent recurrent colonization and infection (SOR: C, expert opinion).